Sticking to common values: Neighbourhood social cohesion moderates the effect of value congruence on life satisfaction. (9th March 2020) - Ponizovskiy, Vladimir; Arant, Regina; Larsen, Mandi; Boehnke, Klaus
Abstract: This article aims to explicate the role of social cohesion in the relationship between adherence to common values and life satisfaction. Shared values are often assumed to be a constitutive element of social cohesion and are used in measurement of the concept. However, sociopsychological theory of values sees social cohesion rather as a moderator of the link between value congruence and life satisfaction, not as a constituent of value congruence. Based on a representative survey of the city of Bremen, Germany ( N = 2605), we predict life satisfaction from person‐group value congruence and neighbourhood social cohesion. We find no relationship between value congruence and social cohesion, but a significant positive moderating effect of social cohesion on the relationship between value congruence and life satisfaction. The findings suggest that sticking to common values does not increase social cohesion, but that positive effects of value congruence are more pronounced in high‐cohesion neighbourhoods.